Impact of dietary Sardinella lemuru fish oil supplementation on egg production and fatty acid profile of laying quails in smallholder farming - Nafisah, Ainun; Wijaya, Gagah Hendra; Romadoni, Fathurrahman Bintang; Fahri, Mochamad; Syafiyullah, Radian; Liany, Kania Asri (Jurnal Ilmiah Pertanian, 2025)
Smallholder quail farms often face limitations in providing high-quality feed that can improve both productivity and nutritional quality of eggs, particularly in enhancing essential fatty acids such as omega-3. Bali sardinella (Sardinella lemuru) fish oil is a rich source of omega-3 fatty acids and holds potential as a dietary supplement to enhance egg nutritional value. This study aimed to evaluate the impact of S. lemuru fish oil supplementation in feed on egg production and fatty acid profile of laying quails under smallholder farming conditions. A randomized block design was applied with four treatments: T0 (0% LFO), T1 (2% LFO), T2 (4% LFO), and T3 (6% LFO), each with two replications and 50 adult female quails per unit. The results showed that S. lemuru fish oil supplementation had no significant effect on egg weight, egg length, viscosity, yolk diameter and height, or other physical egg parameters. However, T3 significantly reduced egg production. The 2% LFO treatment (T1) resulted in the highest crude protein content in the feed and relatively better performance and physical egg quality. The fatty acid profile of eggs was dominated by oleic, palmitic, and linoleic acids, with omega-3 levels increasing in line with higher LFO doses. These findings suggest that 2% S. lemuru fish oil supplementation is suitable for smallholder quail farming to improve egg quality without significantly increasing production costs.